Aging resistance of surface-treated dental zirconia. Issue 2 (February 2015) - Inokoshi, Masanao; Vanmeensel, Kim; Zhang, Fei; De Munck, Jan; Eliades, George; Minakuchi, Shunsuke; Naert, Ignace; Van Meerbeek, Bart; Vleugels, Jozef
Highlights: We assess the rough polished, Al2 O3 or tribochemical silica sandblasted zirconia. These surface treatments improve the aging resistance of Y-TZP zirconia. Ce-TZP/Al2 O3 zirconia are not affected by low-temperature degradation. Surface treatments slightly decrease the aging resistance of Y-TZP/Al2 O3 zirconia. Abstract: The influence of surface treatment on the low-temperature degradation (LTD) of tetragonal zirconia polycrystalline (TZP) is still unclear. Objectives: The effect of surface treatments on the LTD behavior of zirconia was investigated. Methods: Fully-sintered specimens of seven commercial dental zirconia (Aadva, GC; In-CeramYZ, VITA; IPS e.max ZirCAD, Ivoclar Vivadent; LAVA Frame and LAVA Plus, 3M ESPE; NANOZR, Panasonic; ZirTough, Kuraray Noritake) were provided by the manufacturers with specimen dimensions of approximately 10 mm × 5 mm × 3 mm. For each zirconia grade, samples were kept 'as sintered' (untreated) or were subjected to one of the three surface treatments: rough polished, sandblasted with Al2 O3, tribochemical silica sandblasted ( n = 3/group). The tetragonal to monoclinic transformation was evaluated by X-ray diffraction at several intervals during LTD testing up to 40 h in steam in an autoclave (134 °C, 2 bar). Results: The five yttria-stabilized TZP (Y-TZP: Aadva, In-CeramYZ, IPS e.max ZirCAD, LAVA Frame, LAVA Plus) zirconia showed a similar trend in LTD behavior. The Al2 O3 sandblasted zirconia showed the highest monoclinic volume fraction. The as sintered (untreated) zirconia degraded faster than the surface-treated zirconia. Although the surface-treated ceria-stabilized TZP/alumina (Ce-TZP/Al2 O3 : NANOZR) zirconia had a higher initial monoclinic volume fraction compared to the Y-TZP zirconia, it showed a stronger aging resistance. The as sintered (untreated) Y-TZP/alumina (Y-TZP/Al2 O3 : ZirTough) zirconia showed a strong aging resistance, whereas the surface-treated Y-TZP/Al2 O3 zirconia degraded slightly. Significance: Surface treatment improved the aging resistance of Y-TZP zirconia. Surface treatment did not affect the LTD behavior of Ce-TZP/Al2 O3 zirconia, while surface treatment decreased the aging resistance of Y-TZP/Al2 O3 zirconia.